Reoccurrence of West Nile virus lineage 1 after 2-year decline: first equine outbreak in Campania region - de Martinis, Claudio; Cardillo, Lorena; Pesce, Federica; Viscardi, Maurizio; Cozzolino, Loredana; Paradiso, Rubina; Cavallo, Stefania; De Ascentis, Matteo; Goffredo, Maria; Monaco, Federica; Savini, Giovanni; D’Orilia, Francescantonio; et al. (Frontiers in Veterinary Science, 2023)
West Nile Virus (WNV) is the most widespread arbovirus worldwide, being responsible for severe neurological symptoms in humans, as well as horses and birds. The main reservoir and amplifier of the virus are birds, and migratory birds seem to have a key role in the introduction and spread of WNV during their migratory routes. WNV lineage 1 (L1) has been missing in Italy since almost 10 years, to reappear in 2020 in two dead raptor birds in Southern Italy. The present study reports the first equine outbreak in the Campania Region. A 7-year-old horse died because of worsening neurological signs and underwent necropsy and biomolecular analyses. WNV-L1 was detected by real time RT-PCR in the heart, brain, gut, liver and spleen. Next Generation Sequence and phylogenetic analysis revealed that the strain responsible for the outbreak, showed a nucleotide identity over 98% with the strain found in an Accipiter gentilis two years before in the same area, belonging to the WNV-L1 Western-Mediterranean sub-cluster. These results underline that WNV-L1, after the re-introduction in 2020, have probably silently circulated during a two-year-eclipse, with no positive sample revealed by both serological and biomolecular examinations in horses, birds, and mosquitoes. The climate changes that have occurred in the last decades are evolving the epidemiology of WNV, with introductions or re-introductions of the virus in areas that were previously considered at low-risk. Thereby, the virus may easily amplify and establish, to reappear with sporadic evident cases in susceptible hosts after several months or even years.